Known and inferred distributions of beaked whale species (Cetacea: Ziphiidae) - MacLeod , Colin D.; Perrin , William F.; Pitman, Robert; Barlow , Jay; Ballance, Lisa; D'Amico, Angela; Gerrodette, Tim; Joyce , Gerald; Mullin , Keith D.; Palka , Debra L.; Waring , Gordon T. (J. Cetacean Res. Manage., 2023)
Information regarding beaked whales is so sparse that even the most basic aspects of their biology, such as their distribution, remain poorly defined for some species. We have reviewed the known distribution of each beaked whale species and where possible, used this information to infer its global distribution. While for some species, such as the relatively commonly recorded Cuvier’s beaked whale, the inferred distribution is likely to be an accurate reflection of the species’ actual distribution, for other lesser known species, such as the spade-toothed whale, the inferred distribution is more tentative. However, even such limited distribution information is essential when assessing and mitigating potential anthropogenic impacts on beaked whales and serves to highlight gaps in our knowledge that need to be filled if assessment and mitigation are to be successfully conducted.